1996
DOI: 10.1002/(sici)1096-8652(199605)52:1<14::aid-ajh3>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of antithrombin III, protein C, and protein S levels and activated protein C resistance in polycythemia vera and essential thrombocythemia patients with thrombosis

Abstract: Patients with polycythemia vera (PV) or essential thrombocythemia (ET) show a high frequency of thrombosis. The reduction of hematocrit after phlebotomy and normalization of platelet counts do not completely eliminate thrombotic risk. Some preliminary studies reported a reduction in the concentration of natural anticoagulants (NA) in this group of patients. For this reason we evaluated protein S (PS) total antigen, antithrombin III (AT III), and protein C (PC) activity in 81 patients with chronic myeloprolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
38
2
6

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 46 publications
4
38
2
6
Order By: Relevance
“…Thus, Wieczorek et al ®nd decreased levels of protein C and total protein S, while the levels of protein S free and antithrombin were normal [29]. In a study of 81 patients with ET and PCV Bucalossi and co-workers report comparable levels of protein C and S and antithrombin and a signi®cant reduction of protein C activity [28]. In contrast to our ®ndings, they report a de®ciency of anticoagulant proteins in a larger proportion of patients with thrombosis than without thrombosis.…”
Section: Discussioncontrasting
confidence: 82%
“…Thus, Wieczorek et al ®nd decreased levels of protein C and total protein S, while the levels of protein S free and antithrombin were normal [29]. In a study of 81 patients with ET and PCV Bucalossi and co-workers report comparable levels of protein C and S and antithrombin and a signi®cant reduction of protein C activity [28]. In contrast to our ®ndings, they report a de®ciency of anticoagulant proteins in a larger proportion of patients with thrombosis than without thrombosis.…”
Section: Discussioncontrasting
confidence: 82%
“…Although life expectancy approaches normal, chronic myeloproliferative disorder (MPD) patients are characterized by considerable morbidity owing to recurrent thrombohaemorrhagic diathesis, possibly related to disturbances of the coagulation system and multiple platelet abnormalities resulting from clonally derived megakaryocytopoiesis (Bucalossi et al, 1996;Finazzi et al, 1996;Wehmeier et al, 1997). The bleeding tendency may in part be related to an acquired von Willebrand factor (VWF) deficiency associated with consumption of high molecular weight VWF multimers, abnormalities in platelet membrane glycoprotein (GP) and agonist receptor contents and defective agonistmediated platelet aggregation (Kaywin et al, 1978;Mazzucato et al, 1989;Balduini et al, 1991;van Genderen et al, 1997).…”
mentioning
confidence: 99%
“…Likewise, a propensity for thrombosis might be multifactually explained by a variety of abnormalities, implying increased platelet activation such as abnormal eicosanoid metabolism, increased granule secretion as assessed by serological measurement of alpha-granule products and spontaneous platelet aggregation (Cortelazzo et al, 1981;Landolfi et al, 1992;van Genderen et al, 1999;Manoharan et al, 1999). Furthermore, coagulation studies have revealed increased markers of the activated coagulation system and abnormal levels of the natural anticoagulants antithrombin, protein C and protein S in a proportion of patients (Falanga et al, 1994;Bucalossi et al, 1996). Whether the disturbed coagulation predisposing to thrombosis occurs as a consequence of platelet activation remains to be established.…”
mentioning
confidence: 99%
“…10,[13][14][15] In patients with thrombosis, both PCV and factor V Leiden have been associated with factor deficiencies. 13,14 Bucalossi et al reported that of 81 patients with chronic myeloproliferative disorders, at least one natural anticoagulant deficit was detected in 44% of patients with thrombosis versus 6% in patients without thrombosis. 13 They note that many of these patients, like this one, had no apparent family history of hypercoagulability.…”
Section: Discussionmentioning
confidence: 99%